Przekłady literatury polskiej w Słowenii w 2014 roku - Muszyńska‑Vizintin, Anna (Przekłady Literatur Słowiańskich, 2015)
Polish literature in Slovenian translation in 2014 In 2014, 8 Polish authors’ books were translated and published in Slovenia, among which the dominant literary genre was prose: 5 novels written by authors belonging to different generations (Lem, Myśliwski, Huelle, Tokarczuk, Franczak), 2 books on religious topics (on John Paul II and Jerzy Popiełuszko), and a selection of poems by the Polish Nobel Prize winner Wisława Szymborska. Polish literature was also quite present in literary magazines such as „Lirikon21”, „Poetikon”, „Locutio” and „Literatura”. Most of the translations have been published by the most famous and prestigious Slovenian publishers such as Mladinska knjiga, Cankarjeva založba, Celjska Mohorjeva Družba and Beletrina. It is worthy to note that the prestigious award for the best young translator in 2014 was assigned to Staša Pavlović for her first translation, that is, Pawel Huelle’s Mercedes Benz: From Letters to Hrabal. On the basis of the data presented, it can be seen that Polish literature is becoming increasingly popular among Slovenians thanks to the translators and, especially, to their excellent translations. Key words: peripheral cultures, dominant cultures, translations in 2014, translation choices, intercultural dialogue